Shedding New Lights on Javanese Mysticism: Pegon Manuscripts in the Javanese World - Nur Ahmad (Ulumuna, 2019)
This paper aims to understand the Javanese mystical teachings from the Islamic point of views. By examining the development of Javanese mysticism in the suluk literatures, especially those written in Pegon manuscripts, this paper tries to trace back the position of Islam in the mystical dimension of the Javanese people, especially in the idea of waḥdah al-wujūd. This concept teaches the Oneness of God, who is the ultimate source of all existence. Nothing possesses an existence except it is derived from Him. It makes an analogy of creatures and the Creator as the rays of sunshine. Taking all the general Javanese esoteric ideas in the manuscripts studied, the vital point this paper made is that the concept of the unity between the servant and the Lord, which is the deep-rooted doctrine in Java, is genuinely rooted in Islamic teachings. Another finding of this study is concerned with the critical role of pesantren tradition in the dissemination of waḥdah al-wujūd as clearly shown in many Pegon manuscripts. Therefore, the accusation that the “pantheistic” feature in Javanese mysticism is solely attributed to poets, not Islamic scholars, is rejected.